Dinamika Kehidupan Umat Hindu Minoritas Di Kota Palangkaraya: Studi Kasus Pawai Ogoh-Ogoh - Lestari, Yustiva; Hendra, Hendra; Lala, Lala; Yunita, Yunita; Astawa, I Nyoman Sidi; Tarupay, Heri Kusuma (Satya Widya: Jurnal Studi Agama, 2025)
This study aims to examine the dynamics of Hindu life as a minority group in Palangkaraya City through a case study of the implementation of the Ogoh-Ogoh Parade, a religious tradition carried out before Nyepi Day. Using a qualitative approach and case study method, data were collected through observation, interviews, literature studies, and documentation. The results of the study show that the Ogoh-Ogoh Parade is not only a form of spiritual expression of Hindus, but also has social, cultural, and symbolic values ​​in building internal solidarity and interfaith interaction. The implementation of the parade in the 2019–2025 period showed complex dynamics, such as the challenges of the COVID-19 pandemic and adjustments to activities in 2024 to maintain tolerance when coinciding with the beginning of the month of Ramadan. The positive response from the government and the wider community shows support for the existence of Hindu culture as part of local cultural diversity. This study confirms that the Ogoh-Ogoh tradition can be a unifying medium for multicultural society, a means of value education, and a symbol of the empowerment of Hindus in facing challenges as a minority group.